2017
DOI: 10.1097/sla.0000000000002024
|View full text |Cite
|
Sign up to set email alerts
|

Rescuing the Clinical Breast Examination

Abstract: Objective Develop new performance evaluation standards for the clinical breast examination (CBE). Summary Background Data There are several, technical aspects of a proper CBE. Our recent work discovered a significant, linear relationship between palpation force and CBE accuracy. This article investigates the relationship between other technical aspects of the CBE and accuracy. Methods This performance assessment study involved data collection from physicians (n = 553) attending 3 different clinical meeting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…Therefore, we have no reproducible clues of the level of agreement between the different groups with respect to palpation techniques. Specific techniques that might have been handed down by tradition and taught as part of the routine clinical training produce different levels of accuracy [12]. If there is agreement between palpation techniques, the accuracy of palpatory findings can be significantly improved [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we have no reproducible clues of the level of agreement between the different groups with respect to palpation techniques. Specific techniques that might have been handed down by tradition and taught as part of the routine clinical training produce different levels of accuracy [12]. If there is agreement between palpation techniques, the accuracy of palpatory findings can be significantly improved [29].…”
Section: Discussionmentioning
confidence: 99%
“…There is a relationship between search technique, force, and accuracy, as Laufer showed for clinical breast examination (CBE). Her group was able to define a specific range of palpation forces that increase the likelihood of an accurate CBE [12]. Objective assessment of palpation requires assessment methods that are valid, reliable, fair, defensible and evidence-based [13].…”
Section: Introductionmentioning
confidence: 99%
“…Fluidity of motion is a measure of hesitancy, pauses, or changes in direction and ''resets,'' which may be a component of Moulton's ''slowing down,'' 35 or contribute to time spent idle. 36 Tissue handling quantifies the appropriateness of the surgeon's force and tension when manipulating the tissue, 37,38 and varies based on the tissue's friability and fragility. 18 Motion economy is defined as efficiency of movement, or conservation of energy in any trajectory.…”
Section: Rating Scalesmentioning
confidence: 99%
“…The relationship between a person's exploratory techniques and their efficacy is a matter of current study, for example, different methods of palpation movement [7]. An example of stiffness-based palpation is its use in breast palpation for identifying tumors [5], [8]- [10].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the earliest work in palpation skill assessment through sensor recordings was performed on a benchtop model studying pelvic exams [26], where the researchers used force sensors located at strategic points to quantify palpation. Later, clinical breast examination (CBE) and digital rectal examination (DRE) simulators were created using this same approach [5], [8], [29]. These studies have demonstrated that simulators can be effective in assessing aspects of palpation skill.…”
Section: Introductionmentioning
confidence: 99%